Suppression of CHOP Reduces Neuronal Apoptosis and Rescues Cognitive Impairment Induced by Intermittent Hypoxia by Inhibiting Bax and Bak Activation. (23rd August 2021) - Xu, Linhao; Bi, Yanli; Xu, Yizhou; Wu, Yihao; Du, Xiaoxue; Mou, Yixuan; Chen, Jian
Abstract : Our previous study showed that growth arrest- and DNA damage-inducible gene 153 (GAD153/CHOP) plays an important role in intermittent hypoxia- (IH-) induced apoptosis and impaired synaptic plasticity. This study is aimed at determining which signaling pathway is activated to induce CHOP and the role of this protein in mitochondria-dependent apoptosis induced by IH. In the in vivo study, mice were placed in IH chambers for 8 h daily over a period of 2 weeks; the IH chambers had oxygen (O2 ) concentrations that oscillated between 10% and 21%, cycling every 90 s. In the in vitro study, PC12 cells were exposed to 21% O2 (normoxia) or 8 IH cycles (25 min at 21% O2 and 35 min at 0.1% O2 for each cycle). After 2 weeks of IH treatment, we observed that the expression levels of phosphorylated protein kinase-like endoplasmic reticulum kinase (p-PERK), activating transcription factor 4 (ATF-4) and phosphorylated eukaryotic initiation factor 2 alpha (p-elf2 α ), were increased, but the levels of activating transcription factor 6 (ATF-6) and inositol-requiring enzyme 1 (IRE-1) were not increased. GSK2606414, a specific chemical inhibitor of the PERK pathway, reduced the expression of p-PERK, ATF-4, p-elf2 α, and CHOP and rescued ER structure. In addition, Bax and Bak accumulated in the mitochondria after IH treatment, which induced cytochrome c release and initiated apoptosis. These effects were prevented by GSK2606414 and CHOP shRNA. Finally, the impaired long-term potentiation and long-term spatial memory in the IH group were rescued by GSK2606414. Together, the data from the in vitro and in vivo experiments indicate that IH-induced apoptosis and impaired synaptic plasticity were mediated by the PERK-ATF-4-CHOP pathway. Suppressing PERK-ATF-4-CHOP signaling pathway attenuated mitochondria-dependent apoptosis by reducing the expression of Bax and Bak in mitochondria, which may serve as novel adjunct therapeutic strategy for ameliorating obstructive sleep apnea- (OSA-) induced neurocognitive impairment.